Analisis Faktor Pendorong Kecurangan Berbasis Teori Diamond Fraud pada Pemerintah Desa - Lely Kumalawati; Trisna Ayu Oktavia (Journal of Applied Accounting and Taxation, 2020)
The purpose of this study is to describe the perceptions of village government officials regarding the factors driving diamond fraud based fraud. Diamond fraud theory explains the factors of someone committing fraud. The methodology of this research is qualitative, the data used are primary data that is questionnaire. The sample in this study used a purposive sampling method with criteria of 256 employees of the Lumajang district government. The results showed that the perception of village government officials about the factors driving fraud was quite good, with mode 4 which means agreeing with the proxy of the diamond fraud theory.